Website Development Using SDLC Prototyping With Study Case CV. RR Jaya Transindo to Support Brand Trust in Road Freight Transport Services - Shafarani Putri Raissa; Anita Safitri; Nauli Khalila Sherafina (Universitas Negeri Surabaya, 2026)
Newly established B2B road freight transport companies in Indonesia face a critical credibility gap due to the absence of digital presence, limiting their ability to build initial brand trust with potential clients in an increasingly competitive market projected to reach USD 72.25 billion by 2030. This study aims to develop a website for CV. RR Jaya Transindo, a newly established B2B road freight transport company based in Mojokerto, East Java, and to assess user’s perceptions of brand trust based on their interaction with the developed website. A Research and Development (R&D) approach was adopted, applying the SDLC Prototyping model by Pressman and Maxim (2020) through five iterative phases: communication, quick plan, modeling quick design, construction of prototype, and deployment, delivery, and feedback. The website was developed using WordPress CMS with UML-based system modeling. Black-box testing across 31 test cases yielded a cumulative effectiveness score of 100%, confirming full functional conformity. Brand trust was evaluated through a quantitative survey adapted from Mal and Davies (2023) administered to 50 potential B2B clients across East, Central, and West Java. Results produced an overall mean score of 4.44, categorized as very high brand trust, indicating that the website effectively establishes a strong initial trust impression. This study demonstrates that iterative, user-feedback-driven development through SDLC Prototyping produces technically reliable systems capable of supporting initial brand trust formation in B2B road freight transport services.